Investigating Caregiving Dynamics and Subjective Cognitive Decline: An Analysis Using BRFSS Database Insights - Okelue Edwards Okobi; Olayinka Olusola Bolaji; Omolola Okunromade; Chioma J. Anats (Archives of Current Research International, 2024)
Background: Subjective cognitive decline (SCD), characterized by self-reported memory or cognitive difficulties, is an increasing concern among older adults. This study utilizes data from the Behavioral Risk Factor Surveillance System (BRFSS) to examine SCD prevalence, professional consultation patterns, and caregiving dynamics among U.S. adults aged 45 years and older. Objectives: To explore trends in the prevalence of SCD, the extent of professional consultation among those experiencing SCD, and recent caregiving activities. The study aims to identify demographic variations and assess changes over time. Methods: This cross-sectional study analyzes BRFSS data from 2020 and 2022, which includes self-reported data on cognitive symptoms, professional consultation, and caregiving activities. Descriptive statistics and age-adjusted prevalence estimates were computed for SCD, professional consultation, and caregiving activities. Comparative analyses were performed to identify trends between 2020 and 2022, and to assess variations across demographic groups. Results: Between 2020 and 2022, the age-adjusted prevalence of SCD among adults aged 45 and older rose from 9.7% to 11.7%, affecting both genders. Prevalence increased from 9.4% to 11.8% for males and from 10.0% to 11.7% for females. In 2022, Black non-Hispanic adults had a prevalence of 12.2%, Hispanic adults 12.3%, Asian non-Hispanic adults 9.4%, Hawaiian or Pacific Islander non-Hispanic adults 9.9%, American Indian or Alaska Native non-Hispanic adults 21.1%, and Multiracial non-Hispanic adults 19.2%. Professional consultation rates declined from 47.7% to 44.3%. Caregiving for individuals with dementia or cognitive impairment was reported by 22.4% in 2020, decreasing slightly to 21.3% in 2022. General caregiving showed a slight increase from 18.9% to 19.5%. Variations in SCD prevalence and caregiving activities were observed across gender, race, and ethnicity. Conclusion: The study highlights a rising trend in SCD and variations in professional consultation and caregiving dynamics. These findings emphasize the need for targeted public health strategies to address cognitive decline and support caregivers. Enhancing access to healthcare and caregiver resources is crucial for improving outcomes for affected individuals and their caregivers.